Analisis Penggunaan Aplikasi TikTok Sebagai Media Pembelajaran Bahasa Indonesia Dalam Upaya Peningkatan Motivasi Belajar Siswa - Davina Pebrimireni; Diena San Fauziya (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to analyze the impact of using the TikTok application as a medium for learning Indonesian on increasing student learning motivation. TikTok, as a social media platform that is popular among teenagers, offers various features that can be utilized to create interesting and interactive learning content. This research uses a qualitative descriptive method with literature studies accompanied by case studies. The additional technique for collecting this data uses a questionnaire. Data was collected for analysis using qualitative descriptive techniques. The research results show that using TikTok as a learning medium significantly increases students' learning motivation compared to conventional methods. These findings indicate that the integration of social media technology in the learning process can be an effective strategy for increasing student engagement and motivation in learning Indonesian.